Sokolova I. V. Language means of forming motivational comprehension of informative and advertising type of text - Sokolova I. V. (Philological Treatises, 2020)
The article represents results of analysis of the link between motivational aspects of comprehension of informative and advertising type of text and its linguistic parameters. Complex usage of certain language means, determined the system of recipients’ values, is aimed at encouraging recipients to act, modelling their motivational basis and creating a new system of recipients’ values.